2012
DOI: 10.1080/13607863.2012.674486
|View full text |Cite
|
Sign up to set email alerts
|

Setbacks in diet adherence and emotional distress: A study of older patients with type 2 diabetes and their spouses

Abstract: Objectives We investigated patients’ difficulties in managing their diet (i.e., diet setbacks) and associations with change in disease-specific and general emotional distress (diabetes distress and depressive symptoms) among patients with type 2 diabetes and their spouses. Method Data for this study were collected in couples’ homes (N = 115 couples) using structured interviews and self-administered questionnaires at three time points: baseline (T1), six months after baseline (T2), and twelve months after bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
1
17
0
4
Order By: Relevance
“…Studies carried out in the United States (Gonzalez, Shreck, Psaros & Safren, 2015;Hessler et al, 2014;Franks et al, 2012) and Nigeria (Ogbera & Adeyemi-Doro, 2011) have found that people suffering diabetes and distress have a greater risk of presenting low adherence to self-care in comparison with patients who do not.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in the United States (Gonzalez, Shreck, Psaros & Safren, 2015;Hessler et al, 2014;Franks et al, 2012) and Nigeria (Ogbera & Adeyemi-Doro, 2011) have found that people suffering diabetes and distress have a greater risk of presenting low adherence to self-care in comparison with patients who do not.…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining change in diabetes distress following a diabetes education course, having a spouse exhibit more overprotective coping at the outset of education predicted smaller declines in diabetes distress at the end of the course (Hagedoorn et al ., ), and an association between higher spousal overprotection and higher patient diabetes distress was found in another sample of patients with type 2 diabetes and spouses (Schokker et al ., ). A daily diary study revealed on days when spouses engaged in higher than normal levels of diet‐related pressure, which is operationally similar to overprotection, diabetes distress was higher (Stephens et al ., ), and a separate study found a greater shared meal routine, which is conceptually linked with active engagement, predicted reduced diabetes distress for patients (Franks et al ., ; Franks, Sahin et al ., ). Collectively, these studies provide evidence that overprotection from spouses is associated with higher diabetes distress, while active engagement might reduce diabetes distress.…”
Section: Introductionmentioning
confidence: 99%
“…While the developmental‐contextual model of couples coping with chronic illness (Berg & Upchurch, ) supports exploration of this possibility, there has not been extensive exploration of the association between diabetes distress and dietary adherence. One study found that higher patient diabetes distress was correlated with poorer patient dietary adherence and greater dietary setbacks and no evidence was found to suggest dietary adherence predicted later diabetes distress in patients (Franks et al ., ; Franks, Sahin et al ., ), but the longitudinal predictive power of dietary adherence on diabetes distress was not explored. Another study evaluating the impact of diabetes education on glycaemic control in patients with type 2 diabetes found that those patients who experienced steeper declines in diabetes distress also experienced greater improvements in glycaemic control (Zagarins, Allen, Garb, & Welch, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, pressure and persuasion aimed to negatively control spousal behavior leads to increased distress and decreased dietary adherence . Distress and depressive symptoms both increased as patients faced more difficulties in managing their diet (Franks et al, 2012). Spouses' attempts to help their partners regain control and manage their diet as the challenges increased (Franks et al, 2012).…”
Section: Discussionmentioning
confidence: 99%